NATO’s Strategic Ambiguity under Trump: Fallibilism, Alliance Dynamics and Strategic Amnesia - Trevor Graham Ongom; Agfajrina Cindra Pamungkas; Try Danuwijaya (Nation State: Journal of International Studies, 2026)
This article examines how strategic ambiguity within NATO evolved during Donald Trump’s presidency by analyzing the interaction between leadership, institutional political memory, and alliance dynamics. While ambiguity has long existed in alliance politics as a managed feature of deterrence and flexibility, existing scholarship insufficiently explains how alliance commitments themselves become uncertain without formal institutional rupture. To address this gap, the study introduces the concept of strategic amnesia, defined as a leadership-driven suspension of political memory that renders alliance commitments provisional while preserving their instrumental value. The research employs a qualitative interpretive case study grounded in neoclassical realism and informed by pragmatist fallibilism and political memory theory. Using an actor–space–interaction analytical framework, the study analyzes presidential speeches, policy statements, NATO communiqués, and summit interactions from 2016–2026. Interpretive tracing is applied to identify recurring patterns of conditionality and uncertainty in alliance commitments. The findings show that fallibilist leadership traits weakened NATO’s stabilizing political memory by repeatedly reframing collective defense commitments as conditional and negotiable. This produced strategic amnesia, disrupting shared expectations without formal withdrawal from the alliance. The article contributes to debates on uncertainty, political memory, and alliance politics in international relations.